Factors associated with fatigue in CNS inflammatory diseases with AQP4 and MOG antibodies. Issue 3 (18th March 2020) - Yeo, Tianrong; dos Passos, Giordani Rodrigues; Muhammed, Louwai; Everett, Rosie; Reeve, Sandra; Messina, Silvia; Probert, Fay; Leite, Maria Isabel; Palace, Jacqueline
Abstract: Objective: Fatigue is a common and disabling symptom amongst people with multiple sclerosis, however it has not been compared across the central nervous system (CNS) inflammatory diseases associated with aquaporin‐4 (AQP4) and myelin oligodendrocyte glycoprotein (MOG) antibodies (Ab). We explored the factors associated with fatigue within and across the two diseases, and compared fatigue levels between them. Methods: We performed a cross‐sectional study of 90 AQP4‐Ab and 44 MOG‐Ab patients. Fatigue was assessed using the Modified Fatigue Impact Scale (MFIS). Clinical, demographic, and psychometric (anxiety, depression, pain) data were used as independent variables. Multivariable linear regression was used to identify significant independent variables associated with fatigue within and across the two diseases. Results: Within AQP4‐Ab patients, age ( P  = 0.002), disease duration ( P  = 0.004), number of clinical attacks ( P  = 0.001), disability ( P  = 0.007), pain interference ( P  < 0.001), anxiety ( P  = 0.026), and depression ( P  < 0.001) were significant independent variables. Interestingly, disease duration had a negative association with fatigue ( P  = 0.004). Within MOG‐Ab patients, pain interference score ( P  < 0.001) and anxiety ( P  = 0.001) were significant independent variables. Although fatigue was worse in AQP4‐Ab patients compared to MOG‐Ab patients ( P  = 0.008) in all patients as well as in those who ever had transverse myelitis ( P  = 0.023), this was driven by the differences in age, disability and pain interference rather than antibody subtype itself. Interpretation: Multiple factors, but not the antibody specificity, appear to contribute to fatigue in antibody positive CNS inflammatory diseases. A multifaceted treatment approach is needed to better manage the physical, cognitive, and psychosocial aspects of fatigue in these patients.